Laser ignitibility of energetic crystals doped with gold nanoparticles - Churchyard, Sam; Fang, Xiao; Vrcelj, Ranko (Elsevier, 2019)
Laser ignition mechanism enhances the safety of explosive applications. However, optical sensitisation of the energetic materials is required for their optical absorption. In this research, explosive Cyclotrimethylene Trinitramine (RDX) was doped with gold nanoparticles during recrystallisation to provide a suitable optical sensitisation method. The relationship between the precipitation rate used during RDX recrystallisation and the subsequent laser ignition properties using an 808-nm continuous wave diode laser was studied. Faster initial precipitation was found to reduce the laser ignition delay times and smaller nanoparticle size reduced ignition thresholds. It was shown that recrystallized RDX particle size, which is determined by both nanoparticle induced nucleation and precipitation rate, affects the ignition delay time and quality of the crystals. The largest crystals in each batch were investigated using both high-speed photography and microscopic etching, revealing that in contrast to the bulk sample (which was generally a powder), a slower precipitation seems to achieve better doping. The largest crystals in each sample therefore do not represent the bulk sample, a useful indication as such large crystals are easier to handle and therefore tend to be selected for detailed characterisation work.
Keywords: RDX precipitation; Nanoparticles; Plasmon resonance; Laser ignition